Evaluating the effectiveness of a family empowerment program on family function and pulmonary function of children with asthma: A randomized control trial. (August 2016) - Yeh, Hsiu-Ying; Ma, Wei-Fen; Huang, Jing-Long; Hsueh, Kai-Chung; Chiang, Li-Chi
Abstract: Background: Empowerment can be an effective strategy for changing an individual's health behaviours. However, how to empower whole families to manage their children's asthma is a challenge that requires innovative nursing intervention based on family-centred care. Aims: To evaluate the effectiveness of a family empowerment program on family function and pulmonary function of children with asthma compared to those receiving traditional self-management only. Design: A randomized control trial. Methods: Sixty-five families were recruited from one asthma clinic in a medical centre in Taiwan. After random assignment, 34 families in the experimental group received the family empowerment program consisting of four counselling dialogues with the child and its family. We empowered the family caregiver's ability to manage their child's asthma problems through finding the problems in the family, discovery and discussion about the way to solve problems, and enabling the family's cooperation and asthma management. The other 31 families received the traditional care in asthma clinics. The Parental Stress Index and Family Environment Scale of family caregivers, and pulmonary function, and asthma signs of children with asthma were collected at pre-test, 3-month post-test, and one-year follow-up. We utilized the linear mixed model in SPSS (18.0) to analyze the effects between groups, across time, and the interaction between group and time. Results: The family empowerment program decreased parental stress ( F  = 13.993, p  < .0001) and increased family function (cohesion, expression, conflict solving, and independence) ( F  = 19.848, p  < .0001). Children in the experimental group had better pulmonary expiratory flow (PEF) ( F  = 26.483, p  < .0001) and forced expiratory volume in first second (FEV1) ( F  = 7.381, p  = .001) than children in the comparison group; however, no significant change in forced expiratory volume in first second (FEV1)/forced vital capacity (FVC) was found between the two groups. Sleep problems did not show significant changes but cough, wheezing, and dyspnoea were significantly reduced by family caregiver's observations. Conclusion: We empowered families by listening, dialogues, reflection, and taking action based on Freire's empowerment theory. Nurses could initiate the families' life changes and assist children to solve the problems by themselves, which could yield positive health outcomes.